Influence of antigen structure on the activation and induction of unresponsiveness in cloned human T lymphocytes. - Lamb, JR; Feldmann, M; Green, N; Lerner, R (1986)
Using cloned human helper T lymphocytes reactive with a 24 amino acid peptide (p20) of the carboxyl terminal of the HA-1 molecule of influenza haemagglutinin we have investigated the influence of antigen structure on the activation and in the induction of antigen specific unresponsiveness of T cells. For this analysis stereoisomers and structural isomers of p20 have been constructed. P20 in the form of a single loop created by a disulphide based between residue 306 and an additional cysteine at position 330 was able to activate the helper T cells in the presence of accessory cells but unable to induce tolerance. This result suggested that critical residues were prevented from direct interaction with the T-cell receptor and/or the MHC Class II determinants and required processing to expose them. The enantiomer (D-p20) and the inverted sequence (retro-L-p20) which have non complementary side chain topography as compared to the parent peptide neither activated nor tolerized the T cells. Furthermore the retro-D-p20 isomer which has the same side chain topography as L-p20 but with a reversal of amino and carboxyl acid groups also failed to stimulate or tolerize. Therefore T-cell antigen recognition is not determined by side chains alone. The results presented suggest that structure of extrinsic antigen influences T-cell antigen recognition.